Effectiveness of the Koorliny Moort out‐of‐hospital health care program for Aboriginal and Torres Strait Islander children in Western Australia. Issue 5 (21st March 2016) - Cresp, Rebecca; Clarke, Karen; McAuley, Kimberley E; McAullay, Daniel; Moylan, Carolyn A; Peter, Sue; Chaney, Gervase Ml; Cook, Angus; Edmond, Karen M
Abstract: Objectives: To determine whether the Koorliny Moort program could reduce emergency department presentations, hospital admissions and length of stay, and improve attendance at out‐of‐hospital appointments for Aboriginal and Torres Strait Islander children in Western Australia. Design: Children were enrolled in the program from 1 August 2012. Each child acted as their own control. Evaluation data were collected from 1 August 2010 to 31 July 2014. Occasions of service and person‐time in days were compared for each child before and after referral to the program. Setting and participants: Aboriginal children aged 0–16 years residing in three WA regions (Kimberley, Pilbara, Perth metropolitan) who were referred to the Koorliny Moort program. Interventions: Partnerships with primary care providers; nurse‐led care coordination; and outreach care by paediatricians, nurses and social workers closer to the home of the child. Main outcome measures: Emergency department presentations; hospital admissions; length of hospital stay; non‐attended appointments. Results: A total of 942 children were referred to the program. There were significant decreases after referral to the program in the incidence of emergency department presentations (incident rate ratio [IRR], 0.47; 95% CI, 0.43–0.53; P < 0.001), of hospitalisation (IRR, 0.70; 95% CI, 0.62–0.79; P < 0.001), and of non‐attended appointments (IRR, 0.83; 95% CI, 0.74–0.94; P < 0.001), as well as in the mean length of hospital stay (IRR, 0.23; 95% CI, 0.21–0.25; P < 0.001). Conclusions: Health‐seeking behaviour and health outcomes for Aboriginal children can be improved by engaging Aboriginal families in their health care, providing effective communication between health service providers, and delivering a coordinated program of Aboriginal service provider‐led care.